Reductive cleavage of Zn-C bonds by group 14 Zintl anions: synthesis and characterisation of [E9ZnR]3- (E = Ge, Sn, Pb; R = Mes, iPr). - Zhou, B; Denning, MS; Jones, C; Goicoechea, J (2009)
The reaction of ethylenediamine solutions of K(4)E(9) (E = Ge, Sn, Pb) with diaryl and dialkyl organozinc reagents ZnMes(2) and Zn(i)Pr(2) yielded the functionalized Zintl ions, closo-[E(9)ZnR](3-) (R = Mes: E = Ge (1), Sn (2), Pb (3); R = (i)Pr: E = Ge (4), Sn (5), Pb (6)). These reactions proceed via reductive zinc-carbon bond activation of the organometallic reagents by the free solvated electrons present in ethylenediamine solutions of intermetallic Zintl phases. The functionalized cluster anions 1, 2 and 4-6 were characterized in the solid-state as [K(2,2,2-crypt)](+) salts by single-crystal X-ray diffraction and elemental analysis, while the presence of all six cluster anions in solution was confirmed by (1)H and (13)C{(1)H} NMR spectroscopy and electrospray mass spectrometry.